2016
DOI: 10.1002/anie.201609715
|View full text |Cite
|
Sign up to set email alerts
|

Azidoperfluoroalkanes: Synthesis and Application in Copper(I)‐Catalyzed Azide–Alkyne Cycloaddition

Abstract: We report an efficient and scalable synthesis of azidotrifluoromethane (CF N ) and longer perfluorocarbon-chain analogues (R N ; R =C F , C F , C F ), which enables the direct insertion of CF and perfluoroalkyl groups into triazole ring systems. The azidoperfluoroalkanes show good reactivity with terminal alkynes in copper(I)-catalyzed azide-alkyne cycloaddition (CuAAC), giving access to rare and stable N-perfluoroalkyl triazoles. Azidoperfluoroalkanes are thermally stable and the efficiency of their preparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 45 publications
0
65
0
Order By: Relevance
“…Longer-chain azidoperfluoroalkanes wasp repared in an analogousw ay (Scheme 14). [22,23] Azidopentafluoroethane formed using stable pentafluoroethyllithium (Scheme 15), [22] and tetrafluoroethylene-containing azides 6 via organomagnesium compounds generatedb yu sing Turbo-Grignard reagents (Scheme 16). [23]…”
Section: Reactionsoff Luorinated Carbanions With Electrophilic Azide mentioning
confidence: 99%
“…Longer-chain azidoperfluoroalkanes wasp repared in an analogousw ay (Scheme 14). [22,23] Azidopentafluoroethane formed using stable pentafluoroethyllithium (Scheme 15), [22] and tetrafluoroethylene-containing azides 6 via organomagnesium compounds generatedb yu sing Turbo-Grignard reagents (Scheme 16). [23]…”
Section: Reactionsoff Luorinated Carbanions With Electrophilic Azide mentioning
confidence: 99%
“…They have been used for the preparation of different types of heterocycles, N-sulfonyl-containing compounds, [27] and for stereoselectives ynthesiso f2 ,2-diaryl or 2-alkyl-2-aryl-substituted N-sulfonyl enamides ( Figure 1B). [28][29][30][31][32][33] We have recently shown that N-fluoroalkyl triazoles prepared by a[ 3 + +2] cycloaddition of stable and safe azido(per)fluoroalkanes anda lkynes [34][35][36] are efficiently transformed to new N-fluoroalkyl heterocycles via rhodiumc arbenoids. [37,38] However,t he reactivity profiles of Nfluoroalkyl triazoles and N-sulfonyl triazoles are markedlyd ifferent.…”
mentioning
confidence: 99%
“…Triazoles containing ethoxycarbonyl group at position 4 were subjected to basic hydrolysis and decarboxylation to yield 1,5‐disubstituted triazoles in good to high yields (Table ). The reaction complements the copper(I)‐catalyzed azide‐alkyne cycloaddition which gives access to 1,4‐disubstituted triazoles …”
Section: Resultsmentioning
confidence: 98%
“…In sharp contrast, strategies towards the synthesis of N ‐perfluoroalkyl compounds are scarce . Recently, we have reported a new method for the synthesis of azidoperfluoroalkanes (R F ‐N 3 ) which opened new possibilities to access N ‐perfluoroalkyl compounds …”
Section: Introductionmentioning
confidence: 99%